Application Of Android-Based Scms Applications In The Establishment Of Student Character Primary School - Sukaryo, Sukaryo (Prosiding University Research Colloquium, 2021)
This study aims to examine the effectiveness of the application of an Android-based SCMS application in the formation of the character of elementary school students, to describe the character of students in elementary schools, to measure the effectiveness of the application of an Android-based SCMS application in the formation of the character of elementary school students. This research is a type of quantitative research with the subject of elementary school students in Wonosobo district, as well as with the object of students in SD Muhammadiyah Sudagaran Wonosobo. Data collection tools in the form of questionnaires, observations and interviews. The data analysis technique used in this research is descriptive analysis and correlation analysis. The main findings of the study show that the results of the correlation product moment calculation obtained rcount of 0.938 and rtable = 0.514 at a significance level of 5%, meaning that rcount > rtable, then there is a significant influence on the application of the Android-based SCMS application in character building of elementary school students, with a known determination test. that contributes 88% in influencing the character of students.